Uzbekistan : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 2000)
The paper analyzes economic developments and policies over the past couple of years, with emphasis on the period since mid-1998. It assesses consequences for the economy of several external shocks and provides an overview of recent developments. The nature and extent of the external shocks affecting the economy and the internal constraints that characterize the Uzbek economy are detailed. The paper also analyzes the policy responses to these shocks and the results of these policies. A set of tables updates available economic data series.